PEMERIKSAAN HEMOGLOBIN PADA REMAJA PUTRI DENGAN METODE STIK DAN PEMBERIAN SUPLEMEN FE - Wiryanthini, I.A.D.; Wihandani, D.M.; Sutadarma, I.W.G.; Ruma, I.M.W. (Buletin Udayana Mengabdi, 2023)
Blood hemoglobin levels in women of childbearing age are important to prepare a healthy next generation. Low levels of blood hemoglobin or anemia cause disturbances that have long-term impacts on young women and their children, growth is not optimal, prone to stunting, susceptible to infection, reduced intelligence and more prone to poisoning. Implementation of this community service has purpose to improve community health status, especially in adolescent girls, through checking blood hemoglobin levels accompanied by the provision of Fe tablets. Design of this study was cross-sectional descriptive, after checked hemoglobin levels, followed by counseling about anemia in adolescents and distribution of vitamins containing Fe. Respondents consisted of 46 students of class I SMUN 1 Abiansemal Badung who were present during the examination, the prevalence of anemia in students was 23.9%. Therefore, it is still necessary to take preventive measures in the form of counseling and checking blood hemoglobin levels in adolescent girls on an ongoing basis to increase adolescent girls' knowledge about anemia and improve public health status. Keywords: Anemia, hemoglobin, adolescent girls, Fe tablets